Increasing Cadet's Reading Comprehension Through Questioning and Answering Method - Meita Maharani S. (Jurnal Penelitian)
The aims of this research were to find out whether there was a significant difference of cadets’ reading comprehension achievement before and after being taught through questioning and answering method and to find if there was an increase of cadets’ reading comprehension after the instruction. The sample of this research was course TNU 10 A/B in Aviation Polytechnic of Surabaya. The research applied one group pre-test postest design. The result of the reading study by using questioning and answering method showed that there was a significant difference on cadets’ reading comprehension. The average of postest score was higher than that of pre-test, and it has gain. It means that there is an increase of cadets’ reading comprehension achievement after being taught through questioning and answering method type of cooperative learning